Islamic Civilization in Sumatra: History, Progress, and Cultural Dynamics - Eka Farwati; Rama Yani; Nuriah Nuriah; Adinda Febrianti Santoso; Elpia Suryani; Brenda Novita Panjaitan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines Islamic civilization in Sumatra, highlighting three main aspects: the history of the arrival of Islam, its progress, and the development of Islamic culture in the region. Islam first entered Sumatra through international trade routes around the 7th to 13th centuries CE, brought by Arab, Persian, and Indian traders who then interacted with the local population. The spread of Islam was accelerated by the role of Islamic kingdoms such as Samudra Pasai, Aceh Darussalam, and Minangkabau, which became centers for the development of Islamic da'wah and education. The progress of Islam in Sumatra is evident in the growth of religious institutions such as Islamic boarding schools (pesantren) and dayah (Islamic boarding schools), as well as the development of distinctive Islamic science, literature, and architecture. Local culture also experienced acculturation with Islamic values, reflected in customs, customary law, art, and language. This study confirms that Islamic civilization has had a significant influence on the identity and socio-cultural development of Sumatran society to this day.